Kamoshiremasen and Deshou’s Epistemic Modality in Abe Shinzou’s Speech on Covid-19 - Kartika, Diana; Dona, Ulan May; Syahrial, Syahrial; Izmayanti, Dewi Kania (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2023)
This research aims to analyze the structure and meaning and describe the similarities and differences of the epistemic modalities –kamoshiremasen and –deshou in 10 transcripts of Abe Shinzou's speeches at a press conference on covid-19. In this research, the data were collected by means of a literature study from the website of the Japanese Prime Minister's secretarial office, namely www.kantei.go.jpg. To analyze the structure and meaning of the epistemic modality, a qualitative descriptive method is used. Meanwhile, to analyze the similarities and differences using the agih method. Thus, the data is presented in an informal form. This research resulted in the finding that the epistemic modalities –kamoshiremasen and –deshou have similarities, namely they can be attached to verbs, i-adjectives, na-adjectives and nouns and can be placed in the middle and end of sentences. While the difference is the epistemic modality – kamoshiremasen states a possibility and general opinion with a low level of certainty, while the epistemic modality -deshou expresses a conjecture and confirmation with a high degree of certainty. In addition, this study also found an informal epistemic modality, namely kamoshirenai and darou.